Stock Market Exposure and Anxiety in a Turbulent Market: Evidence From China - Qin, Xin; Liao, Hui; Zheng, Xiaoming; Liu, Xin (Frontiers in Psychology, 2019)
The stock market in China has experienced significant turbulence since July 2014, including a bull market. In this paper, we propose that exposure to stock (defined as the condition of being exposed to both stock and stock-related information) can induce anxiety disorder when the market is in a turbulent period. To examine this prediction, we designed two studies in which we operationalized exposure to stock in two different ways. In Study 1, a panel analysis of a longitudinal data set for the Chinese stock market from January 2014 to July 2015 demonstrated that exposure to stock had a significant positive impact on individuals’ anxiety disorder, even in a bull market. Study 2, employing priming experiments, further supported that a temporarily primed “stock mindset” subconsciously increased participants’ anxiety. In addition, Study 2 revealed that physical exercise helped attenuate the detrimental impact of exposure to stock on mental well-being. This research demonstrates the detrimental impact of exposure to a turbulent stock market—even a rising market—on individuals’ mental health. Furthermore, it identifies an effective way to buffer such impact, and suggests ways for social scientists to employ search engines and the related data sets to obtain psychological or behavioral information (especially emotions and emotion disorders) by examining longitudinal “Big Data.”